Counter-Transference and Neutrality: A Challenge for Abortion Counsellor - Soldati, Lorenzo; Bianchi-Demicheli, Francesco; Christian Kohla, John; Andreoli, Antonio; Ortigue, Stephanie; Bitzer, Johannes (Current Women's Health Reviews, 2010)
Introduction: In abortion counselling, the counsellor is generally supposed to be supportive, non-judgmental and neutral. However, counsellors can be confronted with strong internal emotions i.e., counter-transference reactions. Counter-transference may paralyse a counsellor’s investigation and push the counsellor to lose their position of neutrality. Objective: The objective of this article is to show counsellors the importance of integrating counter-transference in abortion counselling to increase the efficacy of their investigation and to maintain a neutral position. Method: A systematic search of the literature was performed. The studies retained for review had to discuss certain aspects of abortion counselling interview techniques, specifically maintaining neutrality and dealing with countertransference. Results: Eight studies matched our criteria. All studies stressed the danger of losing neutrality for the counsellor. A few authors suggested paying attention to this non-conscious process to better help patients. Conclusions: We propose applying the psychoanalytical theory on neutrality and counter-transference to the abortion counselling setting. A cognitive awareness of counter-transference feelings may help the counsellor to understand the non-conscious transference-counter-transference dynamic and to use the moment when neutrality is lost to improve the patient's comprehension of ambivalence.
Keywords: gynaecologist